PERCEPTIONS, ATTITUDES, BEHAVIORS AND POTENTIAL BARRIERS FOR EFFECTIVE OBESITY CARE ACROSS PATIENTS WITH OBESITY (PwO) AND HEALTHCARE PROFESSIONALS (HCPs) IN VIETNAM: FINDINGS FROM AWARENESS CARE AND TREATMENT IN OBESITY MANAGEMENT (ACTION)-VIETNAM STUDY - Tran, Nam Quang; Bich, Dao Nguyen Thi; Nguyet, Thu Nghiem; Anh, Tuan Nguyen; Huu, Nghi Le; Ba, Thanh Dau; Ha, Yousun (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION Increasing obesity rates in Vietnam require timely weight management conversations between HCPs and PwO to help PwO in effective obesity management. The ACTION-IO study reported a lack of awareness of both PwO and HCPs regarding the clinical management of obesity leading to delayed weight management conversations between them. In line with the ACTION-IO study design, the ACTION-Vietnam study (part of the ACTION-APAC study) was designed to identify the perceptions, attitudes, behaviors, and potential barriers to effective obesity management in PwO and HCPs in Vietnam. METHODOLOGY Based on pre-tests conducted in India, Indonesia, Pakistan, Singapore and Thailand to confirm language (English and native languages) and understanding of PwOs and HCPs, an online survey was offered in English and Vietnamese to 1,000 adult PwO (>18 years old, BMI ≥25 kg/m2) and 200 HCPs (general/family practice, internal medicine or appropriate specialty) with >2 years of practice in Vietnam and treated ≥10 PwO in the past month. Pregnant PwO and those involved in intense fitness or body-building programs were excluded from the study. RESULTS All participating PwO (mean age 39.2 years, 50% male) and HCPs (mean age 39 years, 56% male) completed the survey. About 51% of PwO had BMI 25-29.9 kg/m2, 33% had BMI 30-34.9 kg/m2, 12% had BMI 35-39.9 kg/m2 and 5% had BMI >40 kg/m2. About 34% of PwO believed they were either overweight (BMI 25-29.9 kg/m2) or had normal weight. About 60% of PwO strongly agreed that weight loss (WL) was completely their responsibility, and 32% had WL intentions within the next month or committed to/enrolled in a WL program. A majority (82.7%) had attempted WL for an average of four times: 45% regained their weight after maintaining WL for ≥6 months. Only 4% of PwO (n = 40) had ≥10% WL (not due to illness or injury) and had maintained WL for ≥1 year. About 70% of PwO struggled with WL for two years before discussing it with their HCP. The majority (73%) were motivated to initiate WL following conversations with their HCPs, while 43% felt negative emotions. Most participating HCPs (78%) were involved in patient care and medical management (75% non-obesity specialists), and were specialists in internal medicine (24%), general practice (21%), endocrinology (14%) and cardiology (15%). The mean practicing experience was 11.3 years and had seen approximately 30% PwO in the earlier month. The majority agreed that obesity is a chronic disease and should be treated as a team. The majority of HCPs also agreed to support PwO in adopting healthy lifestyle modifications. About 40% of HCPs hesitated to initiate WL discussions, thinking that patients lacked interest in losing weight. HCPs preferred promoting healthy dietary habits and physical activity over anti-obesity medications and rarely prescribed these (16.6%) to PwO. CONCLUSION The findings of the ACTION-Vietnam study emphasize raising awareness for obesity management and suggest early weight management conversations among PWOs and HCPs to prevent obesity-related complications.